Effect of SME’s Managerial Ability and Executive Compensation on Firm Value - Won Park (MDPI AG, 2021)
This paper analyzes the impact of the managerial ability and level of compensation on firm value in small and medium enterprises. The ability of managers is important for the sustainability and growth of small and medium enterprises because they lack awareness of resources, technology, and reputation compared to large enterprises. The managerial ability is the ability to efficiently utilize resources and choose the investment plan with the highest future net cash flows. Managerial ability is also an indicator of the level of compensation for executives. Therefore, the level of executive compensation can help a firm value or growth if it is based on managerial abilities. In addition, high executive compensation standards can be an opportunity or motivation to work hard for the wealth of companies and shareholders. We analyzed 1872 small and medium-sized companies listed on the Korean stock market to achieve the purpose of the research. We analyzed the accounting period of 6 years from 2012 to 2017. Our results have had a positive impact on firm value with executive compensation. In groups with excellent managerial skills, executive compensation has had a positive (+) impact on firm value. However, executive compensation did not have a significant impact on firm value in groups with poor managerial skills. These results validate that the CEO’s role in small and medium enterprise is important and that the level of compensation for executives is important to motivate. It also suggests that executive compensation cannot affect the firm value in groups with low managerial abilities.